Predicting future cash flows: does cash flow have incremental information over accrual earnings? / Tho Lai Mooi - Tho, Lai Mooi (Accounting Research Institute (ARI) & Faculty of Accountancy, 2007)
Financial Reporting Standard No. 107 on cash flow statements in propagating the preparation of cash flow statements as an integral part of an entity’s financial statements, has asserted that ‘cash flow information is useful in assessing the ability of enterprise to generate cash and cash equivalents...’ This study attempts to test this claim by investigating the predictive ability of cash flow from operations versus accrual accounting based data to forecast future cash flow from operations, using multivariate regression models and panel data on a sample of 173 firms listed on Bursa Malaysia. Three predictor variables, net income before extraordinary items (NI), NI plus depreciation and amortisation (NDA) and cash flow from operations (CFO) are used to forecast future cash flows from operations for the period from 1997 to 2005.